Parameter Optimization for the Biodiesel of Xanthoceras sorbifolium Oil and Determination of Fatty Acid Methyl Ester - Liwen Pang; Shanshan Lv; Kaiquan Li; Lijun Ding; Yinan Hao (BioResources, 2022)
Biodiesel was prepared from Xanthoceras sorbifolium Bunge oil and methanol by transesterification with NaOH as the catalyst. The central composite design (CCD) was utilized to optimize its process, and Design Expert software was applied to perform a fitting regression. The best process conditions were determined as: NaOH 0.9%, molar ratio of methanol and oil 7:1, and reaction temperature 62 °C. Under these conditions, the yield of biodiesel was 89.0%. The composition of Xanthoceras sorbifolium Bunge oil-based biodiesel was ascertained by qualitative and quantitative analysis using gas chromatography.